Pengaruh Berjemur Dengan Konsumsi Vitamin C Dan D Terhadap Kadar Hba1c Pada Penderita Diabetes Melitus Tipe II Di Puskesmas Rappokalling - Muh. Faizal Hajarmarup; Masriadi; Hasriwiani Habo Abbas (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
The number of diabetes cases in Makassar continues to increase from year to year and in 2020-2021, diabetes was recorded as the third most common non-communicable disease in terms of cases of 30.976 million patients, Data from the Makassar City Health Office in (2021) cases of Diabetes Mellitus will continue to increase if prevention and control are not improved. This study aims to determine the effect of sunbathing with consumption of vitamins C and D on HbA1C levels in patients with diabetes mellitus II at the Rappokalling Health Center, Makassar. The type of research is quantitative research with a true experiment research design (true experiment) model Pretest-Posttest With Control Group. The study population was all patients with Type 2 diabetes mellitus at the Rappokaling Health Center, Tammua District, Makassar City, South Sulawesi and the research sample was 45 patients with Type 2 diabetes mellitus at the Rappokaling Health Center, Tammua District, Makassar City, South Sulawesi using the purposive sampling method. The results of the study were obtained from data taken by conducting an examination and then conducting a data normality test and analyzing the data using the Wilcoxon test showing that there was an effect of sunbathing on HbA1c levels in patients with diabetes mellitus II at the Rappokalling Health Center in Makassar with a p-value of 0.000 <0.05, Sunbathing with vitamin C consumption with a p-value of 0.001 <0.05 in patients with DM II and sunbathing with vitamin D consumption with a p-value of 0.001 <0.05 in patients with DM II. The conclusion in this study is that there is an effect of sunbathing with vitamin C and D consumption on Hba1C levels in patients with diabetes mellitus II at the Rappokalling Health Center in Makassar. However, it's important to note that this study has some limitations, such as the small sample size and the lack of long-term follow-up, which may affect the generalizability of the findings. Further research is needed to confirm these results.